Factors Explaining Tax Compliance - Lagos Rodríguez, Mª Gabriela (Journal of Finance and Financial Law, 2022)
The aim of the article: The aim is to examine factors explaining tax compliance identified in the Economy to design an efficient tax compliance system. Methodology: In order to achieve the formulated aim, the paper provides an economic literature review on tax compliance related to the efforts of governments to encourage taxpayer compliance while minimizing the cost of a tax administration’s activity. The paper presents a brief laying out the economics of tax evasion. Them, it focuses on critical summaries of what has been learned. Results of the research: The different factors identified indicate that tax compliance is a complex problem, with evident social costs and a significant impact on tax administration decisions. The tax compliance system minimizes the uncertainty and encourages the adoption of a series of voluntary mechanisms for cooperation between taxpayers and the tax administration.